Elevation-driven modifications in tissue architecture and physiobiochemical traits of Panicum antidotale Retz. in the Pothohar Plateau, Pakistan - Muhammad Irshad; Mansoor Hameed; Ummar Iqbal; Muhammad Kaleem; Amina Ameer; Naila Asghar; Eman A. Mahmoud; Fazal Ullah; Ihab Mohamed Moussa; Mohamed Al-Yafrasi; Hosam O. Elansary; Khawaja Shafique Ahmad (Plant Stress, 2024)
Mountainous ecosystems are experiencing rapid shifts in distribution patterns and community structure due to the impacts of climate change and vegetation dynamics. This study offers a comprehensive insight into the adaptive mechanisms of Panicum antidotale to varying elevations within the Pothohar Plateau, shedding light on its survival strategies in climate-affected regions. The findings reveal that populations at lower elevations exhibit maximum height, leaf area, shoot length, and fresh weight, whereas those at higher elevations display significant decrease in these parameters. Moreover, a significant decline in species density, frequency and cover is evident at high elevation. High-elevation populations demonstrate decreased photosynthetic traits, including chlorophyll, carotenoid, and Na and Ca content. Furthermore, there are notable variations in the antioxidant enzyme activity across elevation gradients. Populations at lower elevations exhibit higher activities of superoxide dismutase and peroxidase. Across the gradient, there were significant reductions in root and stem radius, sclerenchyma thickness, bulliform cell size, metaxylem vessels, and phloem area. Populations at moderate elevations displayed thicker lamina and epidermis, larger cortical cells, wider xylem vessels, and increased phloem area; however, these traits declined at higher elevations. High-elevation populations showed thicker lamina and epidermis, extensive sclerenchyma, greater cortical cell area, and higher stomatal density. Photosynthetic traits and enzymatic activity were major contributors at moderate elevations while stem and leaf traits were significantly changed at high elevations. Overall, this research contributes significantly to the broader knowledge of plant adaptation in mountainous ecosystems and stresses the importance of considering elevation as a critical factor in ecological studies.